Complete mitochondrial genome of Anser albifrons frontails (Anseriformes: Anatidae). Issue 2 (3rd July 2018) - Fu, Rong; Dong, Yuanqiu; Xuan, Jun; Liu, Gang; Xiang, Xingjia; Zhou, Lizhi
Abstract: The mitochondrial genome of Anser albifrons frontails is 16740 bp in size, including 22 tRNAs, 2 rRNAs, 13 PCGs, and a CR. Except for tRNA Ser (AGY) and tRNA Leu (CUN) without the dihydrouridine arm, all tRNAs could be folded into canonical cloverleaf structures. All PCGs start with ATG and the termination codon TAA is commonly observed. The CR is located between tRNA Glu and tRNA Phe . The result of the phylogenetic analysis suggests that Anser albifrons frontails is closely related to A. cygonoides and A. anser .